Tribute to Estrellita García Fernández. Body, mind and space-time - Núñez, Beatriz (2023)
The vol. 7, no. 13 of PatryTer – Latin American and Caribbean Journal of Geography and Humanities pays tribute to Dr. Estrellita García Fernández, from the University of Guadalajara and El Colegio de Jalisco, Mexico, who died in July 2023. Estrellita García has joined the PatryTer Scientific Committee since its foundation in July 2017. For seven years, she has contributed to the development of the magazine as an author, to expanding its dissemination and to tasks such as reviewing articles. By dedicating this new issue of PatryTer to Estrellita García, we want to recognize the importance of her intellectual production and professional performance related to Latin American cultural heritage, her link with Cuban and Mexican sciences, but also praise her human quality, as a strong, kind, generous and dedicated to friends.